Driving on ice: Impaired driving skills in current methamphetamine users - Bosanquet, D.; MacDougall, H.; Rogers, S.; Starmer, G.; McKetin, Rebecca; Blaszczynski, A.; McGregor, I. (Springer, 2013)
Rationale: Previous research indicates a complex link between methamphetamine (METH) and driving performance. Acute dosing with amphetamines has improved driving-related performance in some laboratory studies, while epidemiological studies suggest an association between METH use, impaired driving, and accident culpability. Methods: Current METH users were compared to a control group of nonusers on driving simulator performance. Groups were matched for age, gender, and driving experience. Subjects were assessed for current drug use, drug dependence, and drug levels in saliva/blood as well as personality variables, sleepiness, and driving performance. Results: METH users, most of whom met the criteria for METH dependence, were significantly more likely to speed and to weave from side to side when driving. They also left less distance between their vehicle and oncoming vehicles when making a right-hand turn. This risky driving was not associated with current blood levels of METH or its pr incipal metabolite, amphetamine, which varied widely within the METH group. Other drugs were detected (principally low levels of THC or MDMA) in some METH users, but at levels that were unlikely to impair driving performance. There were higher levels of impulsivity and antisocial personality disorder in the METH-using cohort. Conclusions: These findings confirm indications from epidemiological studies of an association between METH use and impaired driving ability and provide a platform for future research to further explore the factors contributing to increased accident risk in this population.